1981
DOI: 10.1037/0021-9010.66.3.314
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of the impact of contingent reinforcement on salespersons' performance behavior.

Abstract: In order to analyze the impact of behavioral technology on service employee performance, a field experiment was conducted in a major department store. Drawn from 16 randomly selected departments, the 82 retail clerk subjects had the same training, performance standards, and at least 6 months experience. Their performance behavior (defined as selling, stockwork, miscellaneous, idle time, and absence from the work station) was measured via direct observation on a random time sampling basis. Both experimental and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 42 publications
1
47
0
3
Order By: Relevance
“…For example (see also Appendix A), when reported increases in productivity due to the reinforcement applications, the interventions focused on reinforcing behavioral responses in a blue collar manufacturing setting that ultimately led to increased production of goods. In addition, when Luthans et al (1981) reported increases in sales performance, they reinforced task-specific behaviors such as the timing of meeting the customer, percentage of restocking the shelves, and average distance from the assigned sales position. As another example of tasks used in this field, Haynes et al (1982) increased safety performance by reinforcing specific driving practices of bus drivers, such as how many times they complied with the traffic signals, which, in turn, led to less accidents in driving city buses.…”
Section: Task Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example (see also Appendix A), when reported increases in productivity due to the reinforcement applications, the interventions focused on reinforcing behavioral responses in a blue collar manufacturing setting that ultimately led to increased production of goods. In addition, when Luthans et al (1981) reported increases in sales performance, they reinforced task-specific behaviors such as the timing of meeting the customer, percentage of restocking the shelves, and average distance from the assigned sales position. As another example of tasks used in this field, Haynes et al (1982) increased safety performance by reinforcing specific driving practices of bus drivers, such as how many times they complied with the traffic signals, which, in turn, led to less accidents in driving city buses.…”
Section: Task Complexitymentioning
confidence: 99%
“…A study also had to examine the dependent variable (s) in the form of behavior-based, task-performance measures. Based on the behavioral management paradigm, every behavior identified for change had to be: (a) observable, (b) measurable, (c) task specific, and (d) performance related (Luthans, Paul, & Baker, 1981;Stajkovic & Luthans, 1997). Using Wood's (1986) theory of task as a theoretical guideline, we defined task performance "in terms of the behavioral responses [italics added] a person should emit in order to achieve some specified level of performance" (p. 62).…”
Section: Inclusion Requirementsmentioning
confidence: 99%
“…This OB Mod model provided a useful and effective framework for both research and application in order to identify, measure, analyze, contingently intervene in, and evaluate employees' performance-related behaviors. Research on this model in a wide range of organizational settings has clearly demonstrated a significant impact on performance improvement (See Stajkovic & Luthans, 1997 for a comprehensive review and meta-analysis and also see published studies over the years such as Luthans, Fox, & Davis, 1991;Luthans, Paul, & Baker, 1981;Luthans, Rhee, Luthans, & Avey, 2008;Peterson & Luthans, 2006;Stajkovic & Luthans, 2001, 2003.…”
mentioning
confidence: 99%
“…Mod.) approach (see Kreitner, 1975, 1985;Luthans et al, 1981;Luthans and Stajkovic, 1999;Peterson and Luthans, 2006;Stajkovic and Luthans, 1997, 2001, 2003. In particular, there is both conceptual (Luthans et al, 1998) and empirical (Welsh et al, 1993) preliminary evidence that the O.B.…”
mentioning
confidence: 99%
“…developed by Luthans and colleagues, and widely tested in the USA (e.g. see Kreitner, 1975, 1985;Luthans et al, 1981;Luthans and Stajkovic, 1999;Peterson and Luthans, 2006;Stajkovic and Luthans, 1997, 2001, 2003 can be successfully applied for performance impact in a cutting-edge Korean internet services firm with all Korean employees. Before presenting the study methods and results, a brief overview of both O.B.…”
mentioning
confidence: 99%